PENGGUNAAN ALAT PERAGA MATERI RENTAN MATEMATIKA SEKOLAH DASAR - Susanti, Mathilda; Sardjana, A; Rosnawati, R (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
Both  the  abstract  mathematical   concept  and who are  in the  stage  of operasional    concrete    thinking    need   teaching   media   to   bridge   the   gap. Teaching  media  is  one  of the  alternatives   used  by teachers  in  elementary schools.   The   objective    of   this   research    is   to   improve    the   learning mathematics  quality  by means  of appropriate  media.This  is action  research   consists  of three  cycles.  The  subject  of the research   is   19  first   grade   students   of  SD  Negeri   Palbapang    J  Bantul Yogyakarta.The result  shows  that  (1) using  the  appropriatte  teaching  media  canimprove   the   students'    activity    in   learning   mathematics.    By   using   the teaching  media,  the  teacher   can  be  more  creative  in solving  the  students' learning  problems.   (2)  The  main  handicap   in using  teaching   media  in the learning   and  teaching   process   is  time   constraint,   lacking   of  media   and teachers     capability      creating      and     developing           media.      (3)     The students'difficulty    in learning  mathematics   can be solved  by teaching  using media.Key words:  media, susceptible teaching  material,  mathematics